Barson_et_al_GenABEL - Barson, Nicola J.; Aykanat, Tuku; Hindar, Kjetil; Baranski, Matthew; Bolstad, Geir H.; Fiske, Peder; Jacq, Céleste; Jensen, Arne J.; Johnston, Susan E.; Karlsson, Sten; Kent, Matthew; Moen, Thomas; et al. (Dryad Digital Repository, 2015)
File in GenABEL format containing SNP genotype and individual phenotype information